Desarrollo de sistema de transporte microencapsulante como alternativa para la solubilidad y estabilidad de fármacos clase IV del SCB - Salazár Miranda, Marco Antonio (Universidad Autónoma Metropolitana, 2018)
Chlorthalidone (CH) is indicated in the management of hypertension either alone or in combination with other antihypertensive drugs, but it displays poor solubility and stability limiting its use in the development of new pharmaceutical alternatives. Spray-drying of double emulsions (SDE) technologies were used for enhancing the stability of CH by using Eudragit L30D-55 (EUD), Opadry II (OPA), or Kollicoat IR (KIR) as wall materials. SDE microcapsules containing CH were evaluated for particle size, morphology, release profiles, accelerated storage, and thermo-oxidative stability. Both types of microcapsules showed higher solubility (>80% in 15 min), lower degradation (<2%) under accelerated storage condition, and lower thermo-oxidative degradation than pure CH. However, SDE microcapsules showed smaller particle sizes (<16 μm) which widens the opportunity of incorporating microcapsules to dosage forms requiring different particle sizes for achieving their functionality. Confirmation of the chemical stability of the substances by conventional techniques does not consider the variations in Ea of the microcapsules, which may influence the performance of the pharmaceutical products. A study of oxidative thermal stability for drugs whose stability is critical, so that it can be discriminated between the formulations in a shorter time and only evaluate the formulations that present higher values of Ea, by an accelerated stability study with a high probability of success. In the development of solid oral dosage forms, it is indispensable to assess the release of the drug from the formulation and its bioavailability. Gastrointestinal dissolution and permeability are fundamental parameters that describe the rate and level of absorption. These analyzes allow the evaluation of oral absorption processes and are used as criteria for the Biopharmaceutical Classification System. In this project, we worked with the continuous kinetic model of in vitro dissolution and permeability to evaluate the effect of the formulation on the absorption of immediate release microencapsulated CH. Analysis of dissolution and permeability results reveal that microencapsulation has improved the solubility of the drug and thus the passage through the membranes of the intestinal epithelium. The average size of the microcapsules was 5 μ. The dissolution profile of the microencapsulated CH with the drug was improved by 80%, the permeated amount (𝐴𝐵𝐶0  ) and the permeation rate (kp) was 7.35 μg / mL and 0.345 min respectively. Based on the above results the microencapsulation technique may be a potential candidate to improve oral absorption of CH in humans.; La CH está indicada en el manejo de la hipertensión sola o en combinación con otros fármacos, pero presenta una baja solubilidad y estabilidad, limitando su uso en el desarrollo de nuevas alternativas farmacéuticas. Se utilizaron tecnologías de secado por aspersión de emulsiones dobles (SDE) para mejorar la estabilidad de CH utilizando Eudragit L30D-55 (EUD), Opadry II (OPA) o Kollicoat IR (KIR) como materiales de pared. Las microcápsulas de SDE que contenían CH se evaluaron en cuanto al tamaño de partícula, morfología, perfiles de liberación, almacenamiento acelerado y estabilidad termo-oxidativa. Las microcápsulas mostraron mayor solubilidad (> 80% en 15 min), menor degradación (menor degradación (<2%) en condiciones de almacenamiento acelerado y menor degradación termo-oxidativa que el CH. La confirmación de la estabilidad química de las sustancias por las técnicas convencionales no tiene en cuenta las variaciones en la energía de activación (Ea) de las microcápsulas, que pueden influir en el desempeño de los productos farmacéuticos. Se empleó el estudio de estabilidad térmica oxidativa para CH cuya estabilidad es crítica, fue útil para discriminar entre las formulaciones y evaluar las formulaciones que presenten mayores valores de Ea comparado con un estudio de estabilidad acelerada con éxito. En solidos orales, es indispensable evaluar la liberación del fármaco de la formulación y su biodisponibilidad. La disolución y la permeabilidad gastrointestinal son parámetros fundamentales que describen la velocidad y el nivel de absorción. Estos análisis permiten evaluar los procesos de absorción por vía oral y son empleados como criterios para el Sistema de Clasificación Biofarmacéutica. En este proyecto, se trabajó con el modelo cinético continuo de disolución y permeabilidad in vitro para evaluar el efecto de la formulación sobre la absorción de CH microencápsulada de liberación inmediata. El análisis de resultados de la disolución y permeabilidad revelan que la microencapsulación ha mejorado la solubilidad del fármaco y por ende el paso a través de las membranas del epitelio intestinal. El tamaño promedio de las microcápsulas fue de 5 μm. El perfil de disolución de la CH microencápsulada con respecto al fármaco mejoró en un 80%, la cantidad permeada (𝐴𝐵𝐶0  ) y la velocidad de permeación (kp) fue 7.35 μg/mL y 0.345 min, respectivamente. Basado en los resultados anteriores la técnica de microencapsulación puede ser un candidato potencial para mejorar la absorción oral de la CH en los seres humanos.